The real-time remote testing and programming of cardiac implantable electronic devices: A case series report - Long, Yu; Xiong, Shiqiang; Tong, Lin; Li, Jin; Luo, Yan; Huang, Wenchao; Zhang, Zhen; Liu, Hanxiong; Cai, Lin (Frontiers in Cardiovascular Medicine, 2022)
Minimizing the number of personnel in the cardiac catheterization laboratory (CCL) and the times of CCL door openings contribute to reduce the infection risk of medical staff and patients, particularly during the COVID-19 pandemic. The usage of 5G-CTP system enables device specialists to conduct remote parameter testing and programming without entering the CCL, potentially reducing the exposure risk of medical staff and patients to COVID-19 infection.